Stimmstörungen - ein Fokus der Klinischen Sprechwissenschaft Aktuelle Beiträge aus Wissenschaft, Forschung und Praxis - Voigt-Zimmermann, Susanne; Kurtenbach, Stephanie; Finkbeinder, Gabriele; Bergt, Anke; Mainka, Wanda (Schriften zur Sprechwissenschaft und Phonetik, 2016)
Working on the voice, whether diagnosticly, therapeuticly, preventively or restoratively, is and will remain one of the core areas of clinical speech science. The authors of this volume provide information on current vocal research results, interdisciplinary projects and central and marginal aspects of the voice, its variability, disease, diagnosis and therapy. For example, it is about the child's handling of the voice, voice training for transsexuals, the aesthetics of radio voices and special phenomena such as yodelling or overtone singing. Susanne Voigt-Zimmermann, Dr. phil., ENT clinic of the Otto von Guericke University Magdeburg. Stephanie Kurtenbach, Dr. phil., Seminar for Speech Science and Phonetics at the MLU Halle-Wittenberg. Gabriele Finkbeiner, Practice for Speech Therapy Oswald, Rüdersdorf near Berlin, Chairwoman of DBKS e. V. Anke Bergt, Lebenshilfe-Werk Weimar / Apolda e. V., deputy chairwoman of DBKS e. V. Wanda Mainka, Neurological Specialist Hospital for Movement Disorders / Parkinson's, Beelitz-Heilstätten.